cDNA sequence and molecular modeling of a nerve growth factor from Bothrops jararacussu venomous gland - Kashima, S.; Soares, A. M.; Roberto, P. G.; Pereira, J. O.; Astolfi, S.; Cintra, A. O.; Fontes, MRM; Giglio, JR; Franca, S. D. (Elsevier B.V., 2002)
The complete nucleotide sequence of a nerve growth factor precursor from Bothrops jararacussu snake (Bj-NGF) was determined by DNA sequencing of a clone from cDNA library prepared from the poly(A) + RNA of the venom gland of B.jararacussu. cDNA encoding Bj-NGF precursor contained 723 bp in length, which encoded a prepro-NGF molecule with 241 amino acid residues. The mature Bj-NGF molecule was composed of I 18 amino acid residues with theoretical pI and molecular weight of 8.31 and 13,537, respectively. Its amino acid sequence showed 97%, 96%, 93%, 86%, 78%, 74%, 76%, 76% and 55% sequential similarities with NGFs from Crotalus durissus terrificus, Agkistrodon halys pallas, Daboia (Vipera) russelli russelli, Bungarus multicinctus, Naja sp., mouse, human, bovine and cat, respectively. Phylogenetic analyses based on the amino acid sequences of 15 NGFs separate the Elapidae family (Naja and Bungarus) from those Crotalidae snakes (Bothrops, Crotalus and Agkistrodon). The three-dimensional structure of mature Bj-NGF was modeled based on the crystal structure of the human NGF. The model reveals that the core of NGF, formed by a pair of P-sheets, is highly conserved and the major mutations are both at the three beta-hairpin loops and at the reverse turn. (C) 2002 Societe francaise de biochimie et biologic moleculaire/Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: nerve growth factor (NGF); Bothrops jararacussu snake; cDNA; molecular model